Brucellosis in a 12-Year-Old Boy in Saudi Arabia: A Case Report for Literature Review - Fahad Al Jarboa, Saleh Almanea, Bader Aldebasi (Pakistan Journal of Medical & Health Sciences, 2022)
Brucellosis is a type of an infection caused by bacteria that affects humans and animals and usually affects the former by drinking unpasteurized milk. This study deals with a clinical case of human Brucellosis. Sudden onset of left hip pain with no history of past trauma, recent URTI, or any other abnormal symptom was examined, and left joint effusion was found. On further investigation, ESR was determined to be 41, and high levels of antibody against Brucella were revealed after the serum agglutination test. Methods to prevent the prevalence of this disease by implementing various measures and creating awareness have also been made.